Happier than Ever: The Role of Public Sentiment in Cryptocurrencies, Meme Stocks, and NFTs - Serada, Alesha (Routledge, 2023)
Investor sentiment is a major factor in financial markets. Long before the GameStop short squeeze and the market-crashing tweets of Elon Musk, social media signals demonstrated credible forecasting, and potentially, manipulative potential in the studies of stock markets and, later, cryptocurrencies. This chapter summarizes the existing research on sentiment in stock markets, cryptocurrencies, and meme stocks and connects it to the productive role of affect in political activism, as conceptualized by Chantal Mouffe. It then proceeds to the current state of the NFT community, with its almost euphorically positive mood. It appears that the valuation of meme stocks and NFTs relies on similar and, sometimes even the same, mechanisms. The collective agreement about their price is guided by the positive sentiment, openly expressed and easily measured online. However, instead of “disrupting the art scene,” an overwhelming positivity in the discourse regarding some assets (e.g., NFTs) has channeled into celebrity culture. With these affective dynamics, the chapter then relates these moods to the concept of affective solidarity.
Keywords: affect; art; digital economy; Mouffe; NFT; positive populism; retail investors; fi=Viestintätieteet|en=Communication Studies|